PREVALENCE OF EXTENDED-SPECTRUM BETA-LACTAMASE PRODUCING ENTEROBACTERIACEAE MEMBERS ISOLATED FROM CLINICALLY SUSPECTED PATIENTS - Kannaiyan, Moorthy; Meseret Abebe, Gedif; Kanimozhi, Chinnasamy; Thambidurai, Punitha; Ashokapuram Selvam, Saranya; Vinodhini, Raja; Suresh, Mickymaray (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Emergence of extended-spectrum beta-lactamases (ESBLs) production poses another clinical problem with Gram-negative bacterial infections. The present study was aimed to evaluate the ESBL producers among various clinical samples of clinically suspected patients. Methods: A total of 1279 samples (urine [918], pus [207] and stool [154]) were collected and 465 isolates (Escherichia coli [320], Enterobacter aerogenes [119] and Klebsiella pneumoniae [26]) were isolated and screened for the presence of ESBL producers using combination disc method and double disc synergy test. Results: Of the 465 culture positive isolates, 130 (E. coli 93 [29.06%], E. aerogenes 35 [29.41%] and K. pneumoniae 2 [7.69%]) were identified as ESBL producers. Among the three Enterobacteriaceae members, E. coli 93 (29.06%) was found to be predominant ESBL producer next in order E. aerogenes 35 (29.41%) and K. pneumoniae 2 (7.69%). Maximum number of ESBL producers were recovered from urine (n=111) followed by pus (n=14) and stool (n=5). All the ESBL-producing isolates were subjected to antibiotic sensitivity test using 10 different antibiotics. ESBL producers were chiefly resistance to ceftriaxone followed by ceftazidime and cefotaxime. Of 130 ESBL producers, 15 (E. coli (8), E. aerogenes (6) and K. pneumoniae (1)] strains were selected for genotypic identification. Among, only two strains of E. aerogenes were positive isolates for CTX-M type ESBL in polymerase chain reaction. Conclusion: This study concluded that among Enterobacteriaceae members, E. coli was the predominant ESBL producers and urine was noted as the prime source for the ESBL positive isolates when compared to other source. Genotypic identification was the best method to differentiate ESBL types which were essential to provide proper treatment.